ANALISIS DESIGN CHASSIS ALAT ANGKUT BUAH SAWIT KAPASITAS 500 KG DENGAN METODE ELEMEN HINGGA: Chassis Design Analysis of Oil Palm Fruit Transportation Equipment Capacity 500 kg using Finite Element Method - Slamet Yuniadi; Iwan Kurniawan (Universitas Negeri Jakarta, 2023)
Currently, the area of oil palm plantations in Indonesia is increasing. However, the condition of oil palm plantations generally has very minimal infrastructure. Therefore, a means of transporting palm fruit is needed that can move in plantation areas that have minimal infrastructure and have the ability to turn with a small turning radius. Chassis is the most important component in every vehicle. Chassis is a component used to support the load, vehicle body, engine, and driver. The development of technology in the field of engineering requires the chassis design of a vehicle to be light but strong. Therefore, this study aims to analyze the strength and safety factor of the chassis using the Finite Element Method. The software used in this analysis is SolidWorks 2018. By doing this analysis, the safety factors in the chassis design will be known. In this design, the magnitude of the factor of safety must be more than two. 3D modeling and material data are required to run the simulation of strength and factor of safety analysis. The material that will be used in the design of this chassis is ASTM A36 steel. From this research, it is expected that the chassis can withstand a maximum load of 500 kg and a maximum driver of 100 kg. From this research, it is expected that the chassis can withstand a maximum load of 500 kg and a maximum driver of 100 kg. From the simulation results using the SolidWorks 2018 software, it can be seen that the safety factor results when accelerating are 3, braking are 3.4 and when turning are 4.2. So it can be concluded that the chassis design is certainly safe.